The Buffering Effect of Mindfulness on Abusive Supervision and Creative Performance: A Social Cognitive Framework - Zheng, Xiaoming; Liu, Xin (Frontiers in Psychology, 2017)
Our research draws upon social cognitive theory and incorporates a regulatory approach to investigate why and when abusive supervision influences employee creative performance. The analyses of data from multiple time points and multiple sources reveal that abusive supervision hampers employee self-efficacy at work, which in turn impairs employee creative performance. Further, employee mindfulness buffers the negative effects of abusive supervision on employee self-efficacy at work as well as the indirect effects of abusive supervision on employee creative performance. Our findings have implications for both theory and practice. Limitations and directions for future research are also discussed.